1995
DOI: 10.1016/0003-2670(95)00030-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequential determination of arsenite and arsenate by ion chromatography

Abstract: A procedure for the sequential determination of arsenite [As(III)] and arsenate [As(V)] based on electrochemical detection for As(II1) and spectrophotometric detection for As(V) following ion chromatographic separation was developed. The color-developing system was based on the ion-association complex formed by heteropolymolybdoarsenic acid with bismuth in the presence of Triton X-100. Experimental conditions for electrochemical detection and color-developing conditions were optimized for A&II) and As(V), resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…This gas can be de com po sed to give ele men tal ar se nic for atomic ab sorp ti on spec tro metry or un der go a co lo ri me tric reac ti on. In dif fe ren ti a ti on stu di es, va ri ous chro ma to grap hic tech ni ques have been used, which are of ten cou pled with ele ment-specific de tec ti on met hods (grap hi te fur na ce ato -mic ab sorp ti on spec tro metry or in duc ti vely cou pled plasma ato mic emis si on spec tro metry) [6][7][8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…This gas can be de com po sed to give ele men tal ar se nic for atomic ab sorp ti on spec tro metry or un der go a co lo ri me tric reac ti on. In dif fe ren ti a ti on stu di es, va ri ous chro ma to grap hic tech ni ques have been used, which are of ten cou pled with ele ment-specific de tec ti on met hods (grap hi te fur na ce ato -mic ab sorp ti on spec tro metry or in duc ti vely cou pled plasma ato mic emis si on spec tro metry) [6][7][8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…We used ascorbic acid in our experiment, which is most economic. Addition of antimony or bismuth in the ion association has been reported to improve sensitivity [20,21]. In our preliminary studies we found that bismuth gives a better absorbance signal than antimony.…”
Section: Color Reactionmentioning
confidence: 84%
“…Li et al [160] analyzed As(III) and As(V) in water by anion exchange chromatography with amperometric and UV detection. It is interesting how the different amperometric response of the two oxidation states complicates the effective possibility of speciating them.…”
Section: Voltammetry Coupled With Nonelectroanalytical Techniquesmentioning
confidence: 99%